2017
DOI: 10.1007/s10461-017-1831-5
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic Characteristics, Sexual and Test-Seeking Behaviours Amongst Men Who have Sex with Both Men and Women: Results from a Bio-behavioural Survey in 13 European Cities

Abstract: Within the MSM population, men who have sex with both men and women (MSMW) are identified as a high-risk group both worldwide and in Europe. In a multi-centred bio-behavioural cross-sectional study, we aimed to assess the relationship(s) between socio-demographic factors, stigma, sexual behavioural patterns, test seeking behaviour and sero-status amongst MSMW. A multi-level analysis was conducted to identify factors associated with being MSMW versus Men who have Sex with Men Only (MSMO). A total of 4901 MSM we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
1
16
2
Order By: Relevance
“…One possible explanation for why MSMW report more mental health problems is their high gender role conflict, which Bingham et al described as ‘internal conflict with traditional gender role stereotypes and an individual’s perceived need to comply with these roles’ 42. In addition, 16.1% (291/1518) of MSM were classified as MSMW in this study, which is higher than the rates observed in 13 European cities (12.64%, 589/4658),22 and nearly 70% of MSMW were married or divorced, in accordance with the results from Zhang et al 43. The Chinese traditional value of ‘having a son to carry on the family name’ may create more stress for MSMW because those who are married may be struggling and caught in a dilemma of whether they should disclose their sexual orientation to their family members.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…One possible explanation for why MSMW report more mental health problems is their high gender role conflict, which Bingham et al described as ‘internal conflict with traditional gender role stereotypes and an individual’s perceived need to comply with these roles’ 42. In addition, 16.1% (291/1518) of MSM were classified as MSMW in this study, which is higher than the rates observed in 13 European cities (12.64%, 589/4658),22 and nearly 70% of MSMW were married or divorced, in accordance with the results from Zhang et al 43. The Chinese traditional value of ‘having a son to carry on the family name’ may create more stress for MSMW because those who are married may be struggling and caught in a dilemma of whether they should disclose their sexual orientation to their family members.…”
Section: Discussioncontrasting
confidence: 66%
“…The Chinese traditional value of ‘having a son to carry on the family name’ may create more stress for MSMW because those who are married may be struggling and caught in a dilemma of whether they should disclose their sexual orientation to their family members. Mirandola et al 22 found that MSMW were less likely than MSMO to be open with their family and friends about their sexual attraction. As a result, MSMW may lack social support, making them vulnerable to mental health problems 44…”
Section: Discussionmentioning
confidence: 99%
“…While weighting appears amply justified, there is considerable debate on how it should be done. The weighting for TLS and RDS surveys has undergone multiple changes [3,4,[8][9][10][11][12][13][14][15][16]22], remains under discussion, or is ignored [23][24][25][26]. For the present, we highlight starfish sampling as a recruitment tool while acknowledging the statistical approaches as a sampling methodology need to be developed in line with those for RDS and TLS.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a gold standard census for many stigmatized populations challenges validation of the different weighting approaches. Often, weighting in RDS and TLS is ignored [11,[23][24][25][26]. For the present first attempt at starfish sampling, we conceptualized the sampling frame as clusters of transmen present at venues with their immediate acquaintances as sampling units with equal probability of inclusion through randomization.…”
Section: Venue-based Sampling Methodsmentioning
confidence: 99%
“…In the survey study of sexual behaviours in 13 European cities, including Warsaw, men who have sex with men and women tended to be less open about their own sexual attraction as compared to men who have sex with men only. Furthermore, 60% of participants declared they would not openly admit their attraction to men [ 12 ]. This indicates that bisexual persons cannot be considered a homogeneous group, in terms of social behaviours.…”
Section: Discussionmentioning
confidence: 99%